Analisis Geser pada Balok Komposit Kayu Kamper Laminasi Baut Perekat-Beton Bertulang dengan Perkuatan CFRP - Pamella M Sri Rezeki; Intan Nuriskha Rachma (Institut Teknologi Garut, 2023)
The cross-sectional dimensions of wood are limited because they experience swelling and shrinkage, so to obtain large wood dimensions, one way to do this is lamination. Laminated wood beams are combined with reinforced concrete plates to produce a structural form where the wood is protected by a concrete plate. The wood lamination system in this research uses adhesive bolts with Carbon Fiber Reinforced Polymer (CFRP) as external reinforcement. The test beam consists of a normal beam without reinforcement (BLN-00) and a test beam with external reinforcement with a CFRP layer (BLF-01). This research was carried out experimentally using the Displacement Control method. The test beam was loaded with a monotonic static concentrated load in the middle of the span with a constant speed of 0.05 mm/s until failure. The results showed that the normal test beam without reinforcement (BLN-00) had a strength of 52.43 kN, stiffness of 7.06 kN/mm, and ductility of 13.42. Meanwhile, the beam with CFRP reinforcement (BLF-01) has a strength of 65.81 kN, stiffness of 9.33 kN/mm, and ductility of 16.85. Apart from that, the maximum shear stress value that occurs in normal beams is 4.23 MPa and in beams with CFRP reinforcement it is 1.95 MPa.